A Corpus-Based Analysis of Lexical Bundles in Traditional and Modern English Fairy Tales (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
Lexical bundles are sequences of words that frequently recur and play a key role in shaping natural language use. Despite extensive research on lexical bundles in academic and spoken registers, their use in literary texts, particularly fairy tales, remains underexplored. As a genre rooted in oral storytelling, fairy tales are characterized by linguistic patterns that may reflect the use of such bundles across different periods. This study aims to identify four-word lexical bundles in traditional and modern English fairy tales, focusing on their frequency, variation, and distribution. Using a corpus-based descriptive-comparative approach, two balanced corpora of 400 traditional and 400 modern fairy tales were analyzed, comprising approximately 2.53 and 2.55 million words, respectively. The bundles were extracted using AntConc based on frequency and dispersion criteria, and analyzed through Key Word in Context (KWIC) and collocate tools to examine variation and recurrent patterns of surrounding words. The findings reveal that lexical bundles are widely used in both corpora. Traditional fairy tales exhibit more bundle types, while modern fairy tales show slightly higher lexical diversity. In terms of variation, most bundles are phrasal and structurally incomplete, functioning as parts of larger syntactic units. Overall, the findings indicate both continuity and subtle change in the use of lexical bundles across the two periods